Le flâneur: un géographe dans la ville ? Sur l’œuvre de Jacques Réda - Soula, Theo (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2021)
Jacques Réda is a french flâneur who explores the city of Paris since the 1970’s. In this article, we would like to show that, somehow, we can compare his poetic works to a geographical study, understanding this expression in a disciplinary way. Wherever poetry is initially far from being compatible with any scientific purpose, researchers have promoted these last years the encounter between literary studies and geography. Réda’s works can illustrate this trend as his writings contain a important spatial dimension. His poetry is indeed strongly realistic, and borrows its realism from a cartographic imaginary. Furthermore, we can compare the area he walks to the « terrain » of a scientist who would make some « relevés topographiques », as Réda says. Finally, the inspiration of the poet come from a geographical conception of the art of writing, placing geography at the heart the artistic process.